The moderating effects of statutory laws and regulations of risk factors and management in the Kingdom of Saudi Arabia construction industries - Rehman, Muhammad Abdul; Ishak, Md Sayuti Bin; Adeleke , Adekunle Qudus (Business, Management and Economics Engineering, 2024)
Purpose – Construction projects are fraught with hazards that have a detrimental impact on schedules, estimates, and quality. The project execution phase exposes contractors to internal and external hazards, either implicitly or explicitly. A project’s achievement is contingent on the proper handling of internal and external hazardous concerns. This study investigates the connection linking internal and external risk factors with risk management in Saudi Arabian contractors and the moderation role of government bylaws linking this connection.Research methodology – This study investigates 303 Saudi Arabian contractors to explain the influence of internal hazards, external hazards, and governmental by-laws on risk management by applying the Partial Least Squares Structural Equation Modeling (PLS-SEM) method.Findings – The outcome indicates that internal hazards (active leadership, team competency, and skills and effective communication), external hazards (technological, political, cultural, and economic factors), and government by-laws (also, its moderation role with external hazards) are positively connected with risk management resulting a moderate effect. Furthermore, the outcome also highlights that the moderating influence of government by-laws with internal risk factors is insignificant.Research limitations – The current research model depicted 74.4% of the overall variation in risk management. Other latent variables can explain the 25.6% remaining overall variation in risk management which can be taken into account for future aspects of effective construction risk management.Practical implications – This study raises the efficiency of Saudi Arabian contractors by improving project output delivery. This study made recommendations to boost risk management usage.Originality/Value – This research was conducted for the first time in the Kingdom of Saudi Arabia, and it is an original work.